Nickel-catalyzed asymmetric transfer hydrogenation - Guo, Siyu (2017)
This thesis describes my work on nickel-catalyzed asymmetric transfer hydrogenation of unsaturated C=C and C=N bonds using various hydride sources. It contains three main parts. Chapter one reported a highly enantioselective asymmetric hydrogenation of a,b-unsaturated esters with a chiral phosphine ligand, (R)-Me-DuPhos. With formic acid and triethyl amine worked as hydrogen source, excellent conversion and enantioselectivity were obtained. Furthermore, deuterium labeling experiments revealed a possible mechanism. I also reported asymmetric transfer hydrogenation of a,b-unsatureated esters with DMF and water as hydride source. Chapter two described asymmetric transfer hydrogenation of cinnamates, beta- dehydroacetamidoesters and hydrazones with acetic acid and indium powder. With nickel/(S)-Binapine or (R)-Me-DuPhos catalytic system, a series of C=C and C=N gave high enantioselectivities. Chapter three reported asymmetric deuteration of a,b-unsaturated esters with deuterium water and indium powder as hydride source. For all the substrates which we tested, excellent conversion, enantioselectivity and deuterium incorporation were obtained. This work provided a novel methodology for fine chiral deuterated products without expensive and explosive deuterium gas. Remove